2017
DOI: 10.1111/spol.12348
|View full text |Cite
|
Sign up to set email alerts
|

“Treading in sand”: A qualitative study of the impact of austerity on inequalities in mental health

Abstract: Successive UK governments since 2010 have adopted policies of austerity characterized by public spending and social security cuts.There has been little qualitative research exploring the effects of these policies on inequalities in mental health. This article presents findings from a case study of Stockton-on-Tees, a local authority in the North East of England with exceptionally high spatial and socio-economic inequalities. Qualitative interviews were undertaken with people experiencing mental health problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Managing the UC digital claims process caused frustration and confusion and adversely affected claimant’s mental health, increasing the possibility of serious self-harm and suicidal ideation, reinforcing other qualitative research on the mental health impact of welfare reform undertaken before UC was rolled out 29 30. Furthermore, punitive deductions pushed vulnerable claimants into debt and destitution, risk of alcohol and substance use relapse, increasing reliance of foodbanks, family and friends.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Managing the UC digital claims process caused frustration and confusion and adversely affected claimant’s mental health, increasing the possibility of serious self-harm and suicidal ideation, reinforcing other qualitative research on the mental health impact of welfare reform undertaken before UC was rolled out 29 30. Furthermore, punitive deductions pushed vulnerable claimants into debt and destitution, risk of alcohol and substance use relapse, increasing reliance of foodbanks, family and friends.…”
Section: Discussionmentioning
confidence: 95%
“…This increase was greater for people with low levels of education, widening inequalities in mental health 42. Recent UK research on mental health, austerity and welfare reform has concluded that cuts in social security are impacting on health through a combination of material and psychosocial pathways that include increased financial hardship and chronic stress 29. Strong associations between debt, depression, mental illness and suicide were identified in a systematic review 43.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Barr et al (2015a) suggest that geographical inequalities in mental health and wellbeing in the UK increased after austerity and that people living in more deprived areas experienced a larger increase in poor mental health ( Barr et al, 2015b ) and self-harm ( Barnes et al, 2016 ). Similarly, qualitative research with people with existing mental health conditions also found that austerity exacerbated their situation ( Mattheys, Warren, & Bambra, 2018 ). Internationally, Karanikolos et al (2013) , Stuckler and Basu (2013) , Niedzwiedz et al (2016) and Helliwell et al, (2017) also found that weakened social protection systems adversely effected mental health in Europe, particularly amongst the most disadvantaged social groups.…”
Section: Discussionmentioning
confidence: 99%
“…Social welfare benefits are hypothesised to improve health-related quality of life, mediated by reduced stress, the adoption of more advantageous social arrangements and healthier behaviours [1]. Yet since 2010, successive governments in the UK have embarked on a programme of austerity, involving cuts to the funding of public services, [2,3] including social welfare benefits. This constitutes the most significant and longest-sustained reduction in state spending since World War II [4].…”
Section: Uk Welfare Contextmentioning
confidence: 99%